Transmission Distance Extension of Directly Modulated Tunable V-cavity Laser Using AWG Wavelength Detuning - Yuan Zhuang; Qiaoli Li; Yiqing Yang; Jianjun Meng; Jiasheng Zhao; Jian-Jun He (IEEE Photonics Journal)
Directly modulated tunable lasers are highly desirable for constructing dense-wavelength division multiplexing (DWDM) access networks, owing to their advantages of low cost, compact size and low power consumption. However, the transmission distance for 10 Gbps is usually limited to about 10 km in the telecom C-band in standard single-mode fiber (SMF) due to wavelength chirp. Here we propose and demonstrate a simple technique for extending the transmission distance by detuning the wavelength of a tunable V-cavity laser with respect to DWDM multiplexers. Experiment results show that 10 Gbps signal can be transmitted error-free (BER<10−12) over 20 km SMF with a wavelength-detuning with respect to a Gaussian-type arrayed waveguide grating (AWG) without dispersion compensation. The power penalty is only 1 dB compared to the back-to-back transmission.